Improving Employee Performance through Digitalization and Skilling Processes - Hadiansyah Hadiansyah; Grahita Chandrarin; Bambang Supriadi (Trescode Green Organization, 2024)
This research aims to describe digitalization, work skills, job satisfaction and employee performance and improve employee performance through the digitalization process and skills in shipping companies. The number of samples in this study was 165 people. The causal relationship between variables will be tested using the SEM analysis model. This research found that the digitalization of shipping companies' departure information and ship arrival notifications creates ease of work, which impacts employee performance in terms of quality and quantity achieved by employees. Work skills for implementing digitalization, such as inaportnet ship services, especially in terms of communication, improve the quality and quantity of employee performance. Thus, increasing employee performance has been influenced by digitalization and skills. Several theoretical and practical implications, as well as implications for further research, this research can contribute to improving employee performance. For policymakers, it becomes input in formulating information and communication technology policies to improve performance in shipping companies. As a suggestion for further research, further research is required to examine the issue of improving employee performance through digitalization and general work skills on cruise ships.